هەڵبژاردنە پەرلەمانیەکەی ٢٠٢١ی عێراق: دادپەروەری لە نوێنەرایەتیکردن و پێداکوتانی زیاتری دیموکراسی - مصطفی, پ.ی.د جلال حسن; محمد, م.ی سەرکەوت فتاح (Sulaimani Journal for Humanities, 2023)
The Iraqi parliamentary elections, held on October 10, 2021, brought about some significant changes compared to the previous elections since 2005. Part of these changes was the result of a new electoral law that increased the number of constituencies from 18 to 83. What we are examining in this research paper is the issue of electoral representativeness, which is linked to the establishment and development of democracy. The main question of this study is: To what extent have the 2021 elections changed the electoral representation process? In our search for an answer to this question, we rely on the latest data released by the Iraqi Independent High Electoral Commission (IHEC) and compare them with the results of the previous Iraqi parliamentary elections since 2005. Investigating the IHEC officially released data, the elections have promoted the process of representation as a pillar of democracy in several ways. This election has created more justice in representing all geographical areas of Iraq, promoted the development and promotion of democracy in the design of constituencies, divided the votes of major forces in such a way that political forces may seldom win all seats, given independents the opportunity to participate in elections efficiently and at a lower cost than before, and strengthened women's representation, with more women winning outside the quota system than in the previous elections. Overall, in this study, we have concluded that compared to other elections in Iraq after 2005, the representation process in the 2021 elections has been fairer and has taken significant steps to advance the democratic process.
Keywords: Key words 2021 elections; electoral representativeness; development of democracy; women representation; strengthening the role of independent MPs